2018
DOI: 10.17236/sat00158
|View full text |Cite
|
Sign up to set email alerts
|

Bovine dilated cardiomyopathy: Almost forgotten but still present

Abstract: Numerous cases of bovine dilatative cardiomyopathy (BDCMP) were registered in the nineteen-eighties, but the prevalence decreased steadily thanks to classical selection measures, i.e. excluding putative carrier animals from breeding. The cases described here show that the recessively inherited disease is still present in the Swiss cattle population. By use of a direct gene test developed a few years ago, a clinical tentative diagnosis can be confirmed. Since the end of the year 2016, carriers are officially la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Not all non-congenital structural cardiac disease in cats fits into the aforementioned categories. Abnormalities include everything from a normal LV with a large LA but normal LV diastolic function using Doppler echocardiography to a grossly malformed LV that defies simple categorization (supplementary files [15][16][17][18]. These cardiac changes have typically been grouped into the class called unclassified cardio myopathy (UCM), a term borrowed from human medicine.…”
Section: Cardiomyopathy -Nonspecific Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…Not all non-congenital structural cardiac disease in cats fits into the aforementioned categories. Abnormalities include everything from a normal LV with a large LA but normal LV diastolic function using Doppler echocardiography to a grossly malformed LV that defies simple categorization (supplementary files [15][16][17][18]. These cardiac changes have typically been grouped into the class called unclassified cardio myopathy (UCM), a term borrowed from human medicine.…”
Section: Cardiomyopathy -Nonspecific Phenotypementioning
confidence: 99%
“…Genetic causes of DCM have also been identified in dogs and cattle. 15 , 16 While one study performed in a research cattery has suggested genetic involvement, that study was undertaken during a time when taurine deficiency was com-mon. 17 No one has yet found a mutational cause of DCM in cats.…”
Section: Dilated Cardiomyopathymentioning
confidence: 99%